Saúde do adolescente na Atenção Básica à Saúde em Guanambi, Bahia: encontros e desencontros para produção do cuidado - Fernandes, Emanuella Soares Fraga (2018)
Adolescence is a phase of life permeated by biopsychosocial transformations and it requires the health services a sensitive view of their needs. Most of the health problems of this population segment can be solved in the scope of Basic Health Care (ABS), and its service unit is a privileged place in the practice of comprehensive care for users in this phase of life. However, this care has not always materialized in the daily reality of these services. Considering this, the present work has as general aim: to analyze the adolescent’s care production of ABS in Guanambi, Bahia, Brazil. As specific objectives: to understand how they process the access the reception and the bond in the care offered to the adolescents in the ABS services; to describe the practices of health professionals regarding adolescent care in ABS, with a perspective on actions at the individual level; to discuss aspects related to the training process of health workers (managers and professionals from ABS) to produce adolescent health care, taking into account academic experience and in-service training. This is a qualitative research approach, which was developed with managers of the Municipal Health Department, as well as professionals and adolescents from five Family Health Units (USF) in Guanambi, Bahia. Data collection was performed with seven managers and 17 primary healthcare professionals between September and November 2017, through semi-structured interviews with a focus group with 10 professionals from the Family Health Support Center (NASF) and five focal group sessions, comprising a total of 47 teen users of the service. Thematic content analysis was used to evaluate the data. The results point out that adolescent access to ABS services occurs undifferentiated amid the unit's demand, and individual adolescent-specific care is not included in the organization of the weekly schedule. Therefore, access to this type of care was mainly directed to a sexual and reproductive perspective and restrictive to women's health. In addition to the organizational and gender barriers, access has been permeated by geographical, technical and symbolic obstacles that end up further distancing the adolescent from the service. Amid these challenges, the community health agent appears in the participants’s speeches of this study as a facilitator of the public's access to ABS services. Reception and bonding are compromised by the professional's unpreparedness in dealing with this public and the way they are treated in the ABS services service is used by the adolescent as a criterion for assessing the quality of care. Regarding the lack of preparation of the professional in the care of this public, the results show an incipient formation in graduation and specialization as well as a lack of permanent education. Thus, it is necessary a greater investment in the training and qualification of health professionalsregarding adolescent care as a way to (re) invent, criticize and improve the practice in ABS services services, favoring the adhesion of this population segment to the proposed actions.